MORPHOGENETIC AND STRUCTURAL CHARACTERISTICS OF GUINEA GRASS PASTURES UNDER ROTATIONAL STOCKING STRATEGIES - Zanine, Anderson De Moura; Nascimento Junior, Domicio; Da Silva, Wilton Ladeira [UNESP]; De Lana Sousa, Braulio Maia; Ferreira, Daniele De Jesus; Teixeira Da Silveira, Marcia Cristina; Parente, Herique Nunes; Rozalino Santos, Manoel Eduardo (Cambridge Univ Press, 2018)
The objective of this study was to evaluate morphogenetic and structural characteristics of Guinea grass pastures subjected to two grazing frequencies (90 and 95% light interception) and two post-grazing heights (30 and 50 cm), during the rainy season and dry year. The leaf appearance rate varied only in the summer, the grazing pastures managed at 90/50 (light interception/post-grazing height) presented higher values in the leaf appearance rate (0.440 leaf/tiller. day), compared with those managed at 90/30 (0.275 leaf/tiller. day) and 95/50 (0.228 leaf/tiller. day), respectively. In the winter/beginning of the spring, pastures managed at 90/30 (0.03 cm/tiller.day) presented lower stem elongation rate in comparison with those managed at 90/50 (0.19 cm/tiller.day) and 95/30 (0.16 cm/tiller.day). Management strategies do not compromise the tissue flow in tillers and, consequently, can be utilized for the management of Guinea grass.